FACTORS CONTRIBUTING TO LOW RESPONSE TOWARDS COVID-19 VACCINATION AMONG RESIDENTS OF ACOO VILLAGE, KOLE DISTRICT. A CROSS-SECTIONAL DESCRIPTIVE STUDY. - Amolo , Monica; Kanyesigye , Richard (Student's Journal of Health Research Africa, 2023)
Background: The main purpose of the study was to determine the factors contributing to low response towards COVID-19 vaccination among residents of Acoo village, Kole district. Methodology: A cross-sectional descriptive study was carried out from December 2022 to March 2023 where a quantitative survey method was used to collect data from A total of 50 respondents were interviewed using questionnaires. The researcher used random sampling techniques to select the respondents for the study. Results: The study revealed that 60% had stopped in primary, therefore they lacked knowledge on COVID-19 as well as vaccine uptake. Fear of the side and adverse effects of covid-19 vaccine led to low vaccine uptake because 95% of respondents hesitated to vaccine uptake because of the side and adverse effects of the vaccine. Low vaccine availability and distribution also contributed to an increase in low covid-19 vaccine uptake, accounting for about 55% of the respondents not being vaccinated. Worst of all, 37.5(75%) of respondents said there was no sensitization about covid-19 vaccine by health workers, therefore leading to insufficient information among residents on covid-19 vaccine hence low uptake of the vaccine. Conclusion. There was a high prevalence of increased covid-19 vaccine hesitancy at 93.3%, and a negative attitude towards covid-19 vaccine uptake was at 63.3%. These were a result of fear of covid-19 vaccine side and adverse effects, Low vaccine availability and distribution, Low level of education, and finally lack of sensitization about covid-19 vaccine. Recommendation; There should be a strengthening of rules and regulations governing vaccine uptake and continuous health education on COVID-19 vaccine hesitancy and its complications. Proper planning on the improvement of continuous distribution and availability of the vaccine at the health facility should be emphasized. Sensitization of residents on covid-19 vaccine should be done to improve vaccine uptake.